IL23R variation determines susceptibility but not disease phenotype in inflammatory bowel disease - Tremelling, M; Cummings, F; Fisher, SA; Mansfield, J; Gwilliam, R; Keniry, A; Nimmo, ER; Drummond, H; Onnie, CM; Prescott, NJ; Sanderson, J; Bredin, F; et al. (Elsevier, 2007)
Background & Aims: Identification of inflammatory bowel disease (IBD) susceptibility genes is key to understanding pathogenic mechanisms. Recently, the North American IBD Genetics Consortium provided compelling evidence for an association between ileal Crohn’s disease (CD) and the IL23R gene using genome-wide association scanning. External replication is a priority, both to confirm this finding in other populations and to validate this new technique. We tested for association between IL23R and IBD in a large independent UK panel to determine the size of the effect and explore subphenotype correlation and interaction with CARD15. Methods: Eight single nucleotide polymorphism markers in IL23R tested in the North American study were genotyped in 1902 cases of Crohn’s disease (CD), 975 cases of ulcerative colitis (UC), and 1345 controls using MassARRAY. Data were analyzed using χ2 statistics, and subgroup association was sought. Results: A highly significant association with CD was observed, with the strongest signal at coding variant Arg381Gln (allele frequency, 2.5% in CD vs 6.2% in controls [P = 1.1 × 10−12]; odds ratio, 0.38; 95% confidence interval, 0.29–0.50). A weaker effect was seen in UC (allele frequency, 4.6%; odds ratio, 0.73; 95% confidence interval, 0.55–0.96). Analysis accounting for Arg381Gln suggested that other loci within IL23R also influence IBD susceptibility. Within CD, there were no subphenotype associations or evidence of interaction with CARD15. Conclusions: This study shows an association between IL23R and all subphenotypes of CD with a smaller effect on UC. This extends the findings of the North American study, providing clear evidence that genome-wide association scanning can successfully identify true complex disease genes.